Agricultural ecosystems and their services: the vanguard of sustainability? - DeClerck, Fabrice A.J.; Jones, S.K.; Attwood, S.; Bossio, Deborah A.; Girvetz, Evan Hartunian; Chaplin-Kramer, Rebecca; Enfors, E.; Fremier, Alexander K.; Gordon, LJ; Kizito, Fred; López Noriega, Isabel; Matthews, Nathaniel; et al. (Elsevier, 2016)
Sustainable Development Goals offer an opportunity to improve human well-being while conserving natural resources. Ecosystem services highlight human well-being benefits ecosystems, including agricultural ecosystems, provides. Whereas agricultural systems produce the majority of our food, they drive significant environmental degradation. This tension between development and environmental conservation objectives is not an immutable outcome as agricultural systems are simultaneously dependents, and providers of ecosystem services. Recognizing this duality allows integration of environmental and development objectives and leverages agricultural ecosystem services for achieving sustainability targets. We propose a framework to operationalize ecosystem services and resilience-based interventions in agricultural landscapes and call for renewed efforts to apply resilience-based approaches to landscape management challenges and for refocusing ecosystem service research on human well-being outcomes.